Republic of Armenia : Financial Sector Assessment Program-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Armenia. (IMF Staff Country Reports; Country Report, 2018)
The Armenian banking sector is recovering from the 2014 economic slowdown, aided by additional capital injected by shareholders, several mergers, and improved regulation and supervision. However, banks, including the largest ones, are vulnerable to external shocks because high levels of dollarization expose them to FX-related credit and liquidity risks. These risks can be mitigated with the adoption of a stressed debt service to income ratio limit, the gradual introduction of reserve requirements in foreign currency for liabilities denominated in foreign currency, and the adoption of the Liquidity Coverage Ratio (LCR) and Net Stable Funding Ratio (NSFR) in domestic currency and in United States dollars (USD). The introduction of the capital surcharge for domestic systemically important banks is also needed.